A Clique based Identification of Wake-Up Nodes against Reactive Jamming Attacks in Wireless Sensor Networks - Shin, Incheol; ., . (International Journal of Engineering and Technology, 2018)
Although there are many countermeasures and mitigation techniques against jamming attacks proposed in literature, those methods still require excessive computational capabilities to wireless devices. Especially, for the most two well-known approaches, frequency hopping and channel surfing techniques, they necessitate excessive computational resources to overcome the attacks. That is, long-term historical countermeasures against the jamming attacks would cause serious side effects in wireless sensor networks (WSNs). In this paper, we propose novel countermeasure against the reactive jamming attacks, one type of wireless DoS(Denial-of-Service) attacks, by the identification of the wake-up nodes whose wireless signal transmission triggers the activation of the jammers. For the efficient identification of wake-up nodes, we exploit the group testing techniques and clique-based methods. Based on this identification, we further reduce the overall computational overhead in WSNs. Theoretical analysis and simulation result show that our solution can efficiently identify the wake-up nodes, which provides an efficient protective mechanism against reactive jamming attacks.Â Â